Smart Home Switch System Using IoT - Rahim, Khairul; Yahaya, Jabbar Al-Fattah (Evolution in Electrical and Electronic Engineering, 2023)
This work aims to design and develop a smart home system integrating the Blynk application using the ESP32 microcontroller with multiple sensors such as a current sensor (ACS712), temperature and humidity sensor, and relays (DHT11). This system is designed to monitor and control various electrical appliances and devices in the home through a smartphone application. The current sensor (ACS712) is used to measure the current consumption of the appliances, while the DHT11 sensor is used to monitor the temperature and humidity in the room. The relays are used to control the power supply to the appliances, and the Blynk application is used to provide a user-friendly interface for controlling the system. The automation feature of the system allows for the scheduling and control of the appliances based on the user’s preferences and the current conditions in the room. Overall, the smart home switch system SHSS provides a convenient and energy-efficient solution for managing and controlling electrical appliances in the home.